2009
DOI: 10.1063/1.3266841
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid states of Tamm plasmons and exciton polaritons

Abstract: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-pro t purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
63
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 17 publications
2
63
0
2
Order By: Relevance
“…Tamm-plasmon (TP) modes appear as localized electromagnetic modes at the boundary between a metal layer and a DBR analogous to purely electronic Tamm-states evolving at a crystal surface. 10 Since the first experimental observation of TP-modes by Sasin et al, 11 various structures based on this fascinating new type of excitation have been theoretically proposed, anticipating, e.g., resonant coupling of TPpolariton states to optical microcavity modes, 12,13 nonlinear effects, such as optical bistability due to field enhancement in hybrid metal/dielectric structures, 14 or integrated circuits based on plasmon-exciton-polaritons. 15 Experimentally, laser oscillation from hybrid metal/semiconductor structures has been observed.…”
mentioning
confidence: 99%
“…Tamm-plasmon (TP) modes appear as localized electromagnetic modes at the boundary between a metal layer and a DBR analogous to purely electronic Tamm-states evolving at a crystal surface. 10 Since the first experimental observation of TP-modes by Sasin et al, 11 various structures based on this fascinating new type of excitation have been theoretically proposed, anticipating, e.g., resonant coupling of TPpolariton states to optical microcavity modes, 12,13 nonlinear effects, such as optical bistability due to field enhancement in hybrid metal/dielectric structures, 14 or integrated circuits based on plasmon-exciton-polaritons. 15 Experimentally, laser oscillation from hybrid metal/semiconductor structures has been observed.…”
mentioning
confidence: 99%
“…Recently it was shown that such channeling of polaritons is possible using hybrid Tamm-plasmon-exciton-polariton modes ͑TPEPMs͒ which are formed under thin metallic stripes deposited on the top of a planar semiconductor microcavity. [9][10][11] TPEPM states are redshifted from the bare cavity polariton modes by several meV, which provides efficient onedimensional confinement. Exciton-polariton transistors, switches, and logic gates based on TPEPMs would operate at gigahertz frequencies, have extremely low switching power, and be easily integrated on a chip.…”
mentioning
confidence: 99%
“…In a related development, it has been predicted that a structure can be designed to exhibit strong coupling between TPPs and exciton polaritons when a metal film is deposited on one of the Bragg reflectors forming the quantum microcavity. 10 Furthermore it has been suggested that by patterning the metal film it would be possible to create a guiding channel for an exciton-polariton condensate, facilitating a method of producing polariton integrated circuits with potential for use in ultrafast information processing. 11 Recently hybrid states of cavity photons and Tamm plasmons have been observed in an organic microcavity with an incorporated thin silver layer.…”
Section: Introductionmentioning
confidence: 99%